La significació política de la Lucrècia de Joan Ramis: reivindicació de les lleis i dels costums de Menorca davant el menyspreu al Tractat d'Utrecht per part del governador James Johnston. - BERMEJO GREGORIO, JORDI (Scripta)
The specific and concrete political significance of the tragedy Lucrècia (1769) by Joan Ramis was yet to be revealed. To address it, we have observed the background of Locke's political liberalism in the piece, the historical and political context of the island of Menorca during the sixties of the eighteenth century, and, finally, the geometric structure of the work and the logical processes that compose it. The result of the political significance of the tragedy can be summarized as, first, a denunciation of the despotic attitude and action of the British Lieutenant Governor James Johnston's refusal to recognize the validity and legality of the Treaty of Utrecht regarding the survival of the traditional Minorcan bons usos e bons costums derived from the foral laws and privileges of the island --both civil and ecclesiastical--; and, second, a plea to his fellow citizens to fight for what Johnston's government was violating: their idiosyncrasy and their freedom as a people.